2016
DOI: 10.1016/j.fertnstert.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse deselection model for human day 3 in vitro fertilization embryos: the combination of qualitative and quantitative measures of embryo growth

Abstract: The proposed model involving both qualitative and quantitative deselection effectively predicts day 3 embryo implantation potential and is applicable to all IVF embryos regardless of insemination method by using PNF as the reference starting time point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 42 publications
1
76
0
Order By: Relevance
“…Such technology has captured the imagination of practitioners as both a research tool (Costa-Borges et al, 2016;Hardarson et al, 2015;Mölder et al, 2015), comparing embryos resulting from various clinical conditions (Balakier et al, 2016;Gurbuz et al, 2016;Hashimoto et al, 2016;Kaihola et al, 2016;Lindgren et al, 2016), and as a potential prognosticator in clinical practice (Adamson et al, 2016;Chen et al, 2016;Kong et al, 2016;Liu et al, 2016;Milewski et al, 2015;Mizobe et al, 2016;Rubio et al, 2014;VerMilyea et al, 2014;Wu et al, 2016aWu et al, , 2016bYang et al, 2014), although some studies negate this (Freour et al, 2015;Wu et al, 2016aWu et al, , 2016b. Bronet et al (2015) even found distinctive morphokinetic differences between male and female embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Such technology has captured the imagination of practitioners as both a research tool (Costa-Borges et al, 2016;Hardarson et al, 2015;Mölder et al, 2015), comparing embryos resulting from various clinical conditions (Balakier et al, 2016;Gurbuz et al, 2016;Hashimoto et al, 2016;Kaihola et al, 2016;Lindgren et al, 2016), and as a potential prognosticator in clinical practice (Adamson et al, 2016;Chen et al, 2016;Kong et al, 2016;Liu et al, 2016;Milewski et al, 2015;Mizobe et al, 2016;Rubio et al, 2014;VerMilyea et al, 2014;Wu et al, 2016aWu et al, , 2016bYang et al, 2014), although some studies negate this (Freour et al, 2015;Wu et al, 2016aWu et al, , 2016b. Bronet et al (2015) even found distinctive morphokinetic differences between male and female embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these morphokinetic variables other studies (11)(12)(13)(14)(15)(16) focused on qualitative markers of cleavage-stage embryos that were associated with a reduced implantation potential and could be used as deselection criteria such as direct cleavage, multinucleation, and abnormal cleavage patterns. In a recently published study (17) another negative prognostic marker emerged, but in a blastocyst-stage embryo.…”
mentioning
confidence: 99%
“…Quantitative parameters were the time from pronuclear fading (PNF) to ive-cell stage and duration of three-cell stage. In conclusion this deselecting method reported as a reliable tool for embryo selection [39]. In a retrospective multicentric study, 1664 intracytoplasmic sperm injection (ICSI) cycles were analyzed.…”
Section: Morphokinetic Algorithms For Prediction Of Embryo Implantatimentioning
confidence: 99%